Sex Differences in Associations of School Connectedness With Adolescent Sexual Risk‐Taking in Nova Scotia, Canada. (June 2014) - Langille, Donald B.; Asbridge, Mark; Azagba, Sunday; Flowerdew, Gordon; Rasic, Daniel; Cragg, Amber
ABSTRACT BACKGROUND Associations of lower school connectedness have been seen with adolescent sexual risk behaviors, but little is known about gender differences with respect to these relationships. Understanding any such differences could contribute to better supporting the school environment to promote youth sexual health. METHODS We used provincially representative cross‐sectional data from 1415 sexually active students in grades 10 to 12 in Nova Scotia, Canada, to determine whether lower school connectedness was associated with students' sexual risk behaviors using multivariate logistic regression, stratifying by sex. RESULTS In boys, lower connectedness was associated with three risk behaviors, having ≥2 partners in the previous year (odds ratio [OR] 1.07; 95% confidence interval [CI] 1.01‐1.13), no condom use at last intercourse (OR 1.06; 95% CI 1.01‐1.12), and having unplanned intercourse due to substance use (OR 1.09; 95% CI 1.03‐1.15). No such associations were seen in girls. CONCLUSIONS These results demonstrate that gender differences may exist for associations of school connectedness and sexual risk behaviors; connectedness may be more important for boys than for girls in this area of adolescent health. Educators should consider gender differences when designing interventions to maximize youth sexual health through school‐based interventions. Further research on school connectedness and risk‐taking should examine genders separately.